Efficacy of decontamination foam on a non-polar hazardous chemical surrogate. (September 2016) - Harding, Brian Z.; Zhang, Bin; Chen, Hao; Mannan, M. Sam
Abstract: The release of hazardous chemicals poses a threat to individuals in the area of a release and to responders who attempt to limit the damage of the release. For a liquid phase spill, the most common decontamination technology is a sodium hypochlorite and water solution. Although this solution has been proven effective against a variety of contaminants, it also has a host of drawbacks. Novel decontamination technologies have been developed for military applications, however, they have not been explored with the same depth in the industrial sector. Therefore, there is a need for an industrial decontamination technology that is noncorrosive, nontoxic, nonflammable, and environmentally safe. Decontamination solutions and foams have the potential to improve hazardous chemical spill cleanup, saving time, money, and lives. This work uses a derivative of cysteine, called N -(tert-Butoxycarbonyl)-L-cysteine methyl ester (TCME), as a surrogate for non-polar hazardous industrial bio-chemicals. Previous work has been done to compare the effect of decontamination foam against other decontamination solutions, however in the work the contaminants were typically polar, thus easily able to dissolve in the foam and react rapidly. In this work, the effect of less polar contaminants is studied, introducing transport limitations as well as reaction limitations. Additionally, this work examines the effect of surfactant on decontamination reactions by using water based decontamination solution and decontamination foam as decon technologies. All experiments were conducted in the liquid phase and results were analyzed using GC-MS to determine the extent of reaction. Highlights: Decontamination of an analog for hazardous industrial bio-chemicals. Study of the decontamination reaction using non-polar contaminants. Study of the effect of surfactant on decontamination reaction. Use of GC-MS to determine the extent of decontamination reaction.